Kirekesztés vagy befogadás? A nemek és generációk jellegzetességei az információs technológiák használatában és megítélésében - Nagy, Beáta (Szociológiai Szemle, 2024)
The article seeks to understand the effect of two decisive factors, gender and generation, on the active use of the tools of information society. We assume that both women and older generations are less interested in using the information technology, that is they use them less often and besides their attitude to the new technology is more conservative. Two dataset have been analyzed in order to clarify the generational and gender effect; the TARKI survey has covered the whole Hungarian situation, while the research activity carried out in he Kaposvár county have referred to regional level, but offered the opportunity to gain deeper explanations.The diffusion has effected the generations differently, but it has not been valid for women. The latter group has used information technology in a more instrumental way. The most influential variable has been the educational level and the active attachment to the labour market. Thus we can add one more item to the latent functions of employment, elaborated by Marie Jahoda; employment (and educational institutions) offer people the chance to be included into information society. However, after analyzing the attitudes connected to the use of information society, we could observe a rather considerable gap between genders and generations.